Les images animées au Musée de l’histoire de l’immigration, des dispositifs pour le patrimoine immatériel de l’immigration ? - Marie Caquel (Conserveries Mémorielles)
The museum of the history of immigration opened its doors in the Palais de la Porte dorée in 2007, without pre-existent collection. Today, the moving pictures are very present in the permanent exhibition called "Repères", under the shape of photographic movies, archives images, filmed testimonies and contemporary artists videos. Describing these devices we want to show that frontiers between disciplines and its approaches to transmit an immaterial heritage are not seals. Above all such an heritage is not obtain by the most expected disciplines (history, sociology), but by a more surprising couple: ethnology and contemporary art.